Ok...let's see,
csc(theta) = 1/sin(theta)
sin (90 + theta) = sin(90) cos(theta) + sin(theta)cos(90)
= cos(theta)
so,
1/sin(90+theta) = 1/cos(theta) = sec(theta)
Good luck!
2006-12-17 14:16:58
·
answer #1
·
answered by alrivera_1 4
·
0⤊
0⤋
From the left :
= csc(90º+θ)
= 1 / sin( 90º + θ) ( from definition of csc)
= 1 / cos (θ) ( sin( 90º + θ) = cos(θ) )
= secθ (definition for secθ)
and that equals the right side. That's it !
2006-12-17 14:15:03
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
csc(90º + θ) = sec θ
To solve, use the reciprocal identity for csc
1/sin(90º + θ) = sec θ
Use the addition formula sin (A + B) = sin A cos B + cos A sin B
1/(sin 90º cos θ + cos 90º sin θ) = sec θ
Use the following identities: sin 90º = 1 and cos 90º = 0.
1/(1 · cos θ + 0 · sin θ) = sec θ
Thus,
1/cos θ = sec θ
Therefore,
sec θ = sec θ. QED.
^_^
2006-12-17 19:32:20
·
answer #3
·
answered by kevin! 5
·
0⤊
0⤋
csc θ = 1/sin θ i.e. csc(90º+θ) = 1/sin(90º+θ)
sec θ = 1/cos θ
So, we have,
1/sin(90º+θ) = 1/cos θ
or, cos θ = sin (90º+θ)
I hope this helps
2006-12-17 16:30:35
·
answer #4
·
answered by Renaud 3
·
0⤊
0⤋
csc=1/sin
sin (a+b)=sin a *cos b +cos a *sin b
sin (90+t)=sin 90 * cos t + cos 90 * sin t
sin 90=1
cos 90=0
sin (90+t)=cos t
csc(90+t)=1/sin(90+t)=1/cos t=sec t
2006-12-17 14:34:34
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
csc(90 + A) = sec(A)
1/(sin(90 + A)) = 1/cos(A)
you can also write it as
sin(90 + A) = cos(A)
sin(90 + A) =
sin(90)cos(A) + cos(90)sin(A) =
1cos(A) + 0sinA =
cosA
so
sin(90 + A) = cos(A)
or in our case
csc(90 + A) = sec(A)
2006-12-17 15:44:04
·
answer #6
·
answered by Sherman81 6
·
0⤊
0⤋
csc(90+θ)=secθ
1/(sin(90+θ))=secθ
1/(sin90cosθ+cos90sinθ)=secθ
1/(1*cosθ+0*sinθ)=secθ
1/cosθ=secθ
secθ=secθ
solved!!!
2006-12-17 14:19:33
·
answer #7
·
answered by fortman 3
·
0⤊
0⤋